2019
DOI: 10.1021/acs.jpclett.9b01433
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Exciton Delocalization Enhancement in Multilayer Chiral Linker/Quantum Dot Structures

Abstract: The control of complex devices on the nanoscale is challenging. The development of nanoparticles, such as quantum dots, that serve as "artificial atoms" enables the manipulation of energy levels at the nanoscale. Using quantum dots and wet chemistry, multilayer structures with unique coupling properties can be realized. The coupling of such quantum dots is essential for several applications, such as parallel computing. Earlier work showed enhancement of the delocalization using covalent bonds and short linkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…Similar effect were observed for FeS 2 QDs capped by L/D-cysteine which can assemble within chiral hydrogels Reprinted with permission from a study by Fridman et al [133]. Copyright 2019 American Chemical Society.…”
Section: /-supporting
confidence: 61%
See 1 more Smart Citation
“…Similar effect were observed for FeS 2 QDs capped by L/D-cysteine which can assemble within chiral hydrogels Reprinted with permission from a study by Fridman et al [133]. Copyright 2019 American Chemical Society.…”
Section: /-supporting
confidence: 61%
“…The CISS effect also allows for controlling the electron transfer between QDs in a multilayer structure ( Figure 14C) [133]. In CdSe QD layers connected by chiral linkers, PL decay time under excitation by right circular polarized light is 3.5 times longer than under excitation by left circular polarized light.…”
Section: Spintronicsmentioning
confidence: 99%
“…We have chosen as a reference molecular system a polyglycine α-helix with its D-(D-Gly) and L-(L-Gly) enantiomers and a length of 15 Å. This oligomer length is roughly of the same order of magnitude as in some experimental studies, 60 but shorter as in AFM experiments. 54 The two top panels of Figure 1 show the two enantiomers.…”
mentioning
confidence: 99%
“…In recent years it was found that current passing through chiral molecules exhibits spin preference, an effect known as the Chiral Induced Spin Selectivity (CISS) effect. It is known that this spin-filtering effect may affect the coupling between semiconductor nanocrystals (Quantum Dots, QDs). Indeed, it was shown that for samples of CdSe heterosized QDs, coupled via chiral linkers, an enhancement in the electron wave function delocalization as a function of the induced excited spin direction was observed . In other words, when the excited spin direction agrees well with the organic linker chirality, the coupling strength of the neighboring QDs increases, facilitating energy distribution between the dots even through a long chiral molecule (2.2 nm).…”
mentioning
confidence: 99%